Does aid support democracy? A systematic review of the literature - Rachel M. Gisselquist; Miguel Ni\~no-Zarazúa; Melissa Samarin (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
This study draws on a rigorous systematic review-to our knowledge the first in this area-to take stock of the literature on aid and democracy. It asks: Does aid-especially democracy aid-have positive impact on democracy? How? What factors most influence its impact? In so doing, it considers studies that explicitly focus on 'democracy aid' as an aggregate category, its subcomponents (e.g. aid to elections), and 'developmental aid'. Overall, the evidence suggests that i) democracy aid generally supports rather than hinders democracy building around the world; ii) aid modalities influence the effectiveness of democracy aid; and iii) democracy aid is more associated with positive impact on democracy than developmental aid, probably because it targets key institutions and agents of democratic change. The review presents a new analytical framework for considering the evidence, bringing together core theories of democratization with work on foreign aid effectiveness. Overall, the evidence is most consistent with institutional and agentbased theories of exogenous democratization, and least consistent with expectations drawn from structural theories that would imply stronger positive impact for developmental aid on democratization.
Keywords: D72; F35; F55; 330; foreign aid; democracy; systematic review; democracy aid; democracy assistance; democracy promotion; democratization